Dependency Rates and Savings Rates: Comment. - Gupta, Kanhaya L. (American Economic Review, 1971)
In a recent issue of this Reviewv, Nathaniel Leff examlined the role of demographic factors in the deternmination of aggregate savings rates, using, international cross-section data. His major conclusion was . that dependency ratios are a statistically distinct and quantitatively important influence on aggregate savings ratios, both for the 74 considered as a whole and within the subsets of developed and underdeveloped countries (pp. 893-94). In this note, we shall present evidence showing that, contrary to Leff's findings, dependency ratios play an insignificant role in determining savings rates in the majority of the underdeveloped countries. In a recent paper, I argued and showed that the treatment of underdeveloped as a single group is not very meaningful. In fact, very often such a treatment conceals more information than it reveals. It was then argued that a nmore satisfactory way is to subdivide these according to per capita income levels. Following the classification adopted in that paper, I divided the underdeveloped into three groups: (I) those with per capita income between $0-124; (II) those between $125-249; and (III) those between $250675.' Table 1 gives the identification of the in each group. Using Leff's data, we estimated his equations for each group separately and for the three groups combined together. The equations are: